Fasting serum C-peptide is useful for initial classification of diabetes mellitus in children and adolescents - Min Jung Cho; Min Sun Kim; Chan Jong Kim; Eun Young Kim; Jong Duk Kim; Eun Young Kim; Dae-Yeol Lee (Korean Society of Pediatric Endocrinology, 2014)
PurposeWith rising obesity rates in children, it is increasingly difficult to differentiate between type 1 and type 2 diabetes mellitus (T1DM, T2DM) on clinical grounds alone. Using C-peptide as a method of classifying diabetes mellitus (DM) has been suggested. This study aimed to find a correlation between fasting C-peptide level and DM types in children and adolescents.MethodsA total of 223 diabetic children, newly diagnosed at 5 hospitals between January 2001 and December 2012, were enrolled in this study. Initial DM classification was based on clinical and laboratory data including fasting C-peptide at diagnosis; final classification was based on additional data (pancreatic autoantibodies, human leukocyte antigen type, and clinical course).ResultsOf 223 diabetic children, 140 were diagnosed with T1DM (62.8%) and the remaining 83 with T2DM (37.2%). The mean serum C-peptide level was significantly lower in children with T1DM (0.80 ng/mL) than in children with T2DM (3.91 ng/mL). Among 223 children, 54 had a serum C-peptide level <0.6 ng/mL; they were all diagnosed with T1DM. The proportion of children with T2DM increased in accordance with C-peptide level. Forty-nine of 223 children had a C-peptide level >3.0 ng/mL; 48 of them (97.9%) were diagnosed with T2DM.ConclusionIn this study, we found that if the C-peptide level was <0.6 ng/mL at diagnosis, T2DM could be excluded; if C-peptide level was >3.0 ng/mL, a T1DM diagnosis is unlikely. This finding suggests that serum fasting C-peptide level is useful for classifying DM type at the time of diagnosis in youth.